Empowering UMKM Through Financial Management And Marketing Training Program: Case Study In South Kalimantan Province - Fajriyati, Ilisa; Ambarwati, Riris (PT Inovasi Pratama Internasional, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in regional economic growth, including South Kalimantan. However, the low level of understanding of financial management and utilization of marketing technology is a major obstacle to increasing the competitiveness of MSMEs. This study examined the effects of financial management and marketing training on MSME empowerment in the region. Using a quantitative approach with an explanatory method, data were collected through a closed questionnaire from 100 MSME actors who participated in the training. The results of the multiple linear regression analysis showed that financial management training (β = 0.465; p = 0.001) and marketing training (β = 0.387; p = 0.003) had a positive and significant effect on MSME empowerment. Both variables simultaneously explained 67.4% of the variation in empowerment (R² = 0.674). This finding confirms that structured training is an effective intervention for encouraging independence, increasing assets, and increasing market access for MSME actors. This study provides a practical contribution to the formulation of MSME empowerment policies through need-based training programs